Ultrastructural study of endocytosis of Chlamydia trachomatis by McCoy cells. - Hodinka, R L (1988)
The entry of Chlamydia trachomatis into McCoy cells (fibroblasts) was studied by transmission electron microscopy. On adsorption of elementary bodies (EBs) to host cells at 37 degrees C, the EBs were bound primarily to preexisting cell-surface microvilli. They were also observed in coated pits located at the bases of the microvilli and along smooth surfaces of the host cells and were internalized within coated vesicles at this temperature. Postembedding immunogold labeling on Lowicryl thin sections with anti-clathrin antibody as the primary reagent revealed the gold marker localized in pits and vesicles containing chlamydiae. Some EBs were present in smooth-surfaced invaginations at or near the bases of microvilli and in vesicles devoid of distinguishable coat material. A similar entry process was observed with centrifugation-assisted inoculation of EBs onto the McCoy cells. Individual EBs were initially internalized into tightly bound endocytic vesicles. However, within 1 to 3 h postinfection, multiple C. trachomatis EBs were observed in large, loosely bound vesicles. Evidence suggests that vesicles containing C. trachomatis may have fused with one another early in the infectious process. These results indicate that chlamydiae can exploit the specific process of adsorptive endocytosis for entry into host cells and for translocation to a given intracellular destination, which may be different for each species.